Abscisic acid‐mediated sugar responses are essential for vegetative desiccation tolerance in the liverwort Marchantia polymorpha. Issue 2 (18th April 2023) - Khatun, Nobiza; Shinozawa, Akihisa; Takahashi, Kosaku; Matsuura, Hideyuki; Jahan, Akida; Islam, Mousona; Karim, Masudul; Sk, Rahul; Yoshikawa, Mikako; Ishizaki, Kimitsune; Sakata, Yoichi; Takezawa, Daisuke
Abstract: Low‐molecular‐weight sugars serve as protectants for cellular membranes and macromolecules under the condition of dehydration caused by environmental stress such as desiccation and freezing. These sugars also affect plant growth and development by provoking internal signaling pathways. We previously showed that both sugars and the stress hormone abscisic acid (ABA) enhance desiccation tolerance of gemma, a dormant propagule of the liverwort Marchantia polymorpha . To determine the role of ABA in sugar responses in liverworts, we generated genome‐editing lines of M . polymorpha ABA DEFICIENT 1 (Mp ABA1 ) encoding zeaxanthin epoxidase, which catalyzes the initial reaction toward ABA biosynthesis. The generated Mp aba1 lines that accumulated only a trace amount of endogenous ABA showed reduced desiccation tolerance and reduced sugar responses. RNA‐seq analysis of sucrose‐treated gemmalings of M . polymorpha revealed that expression of a large part of sucrose‐induced genes was reduced in Mp aba1 compared to the wild‐type. Furthermore, Mp aba1 accumulated smaller amounts of low‐molecular‐weight sugars in tissues upon sucrose treatment than the wild‐type, with reduced expression of genes for sucrose synthesis, sugar transporters, and starch‐catabolizing enzymes. These results indicate that endogenous ABA plays a role in the regulation of the positive feedback loop for sugar‐induced sugar accumulation in liverworts, enabling the tissue to have desiccation tolerance.